ORGANISASI PENDIDIKAN DALAM PERSPEKTIF AL-QUR'AN - ARROYAN, MUHAMMAD; Untung, Slamet; Mustakim, Zaenal (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2024)
Organisation is a fundamental necessity for humanity, helping individuals to achieve shared objectives in various areas, including education. Management serves as an important tool in ensuring that organisations operate effectively and productively. This research discusses the organisation of education from the perspective of the Qur’an, emphasising the significance of a clear structure and division of tasks, as well as adaptability to change. The Qur’an, through the concept of